Comprehensive analysis of combustion behavior, kinetics, and gas emissions of fungus bran biofuel through torrefaction pretreatment and polypropylene addition - Guo, Shuai (2024)
This study explored the combustion behavior of co-torrefied biofuel derived from a novel combination of hybrid biomass and plastic waste. With the advanced thermogravimetric-Fourier transform infrared spectroscopy (TG-FTIR), the effect of waste polypropylene (PP) addition and co-torrefaction pretreatment on the combustion characteristics, reactivity, gaseous product release, and pelletization characteristics of Ca-rich fungus bran (FB) biofuel were systemically investigated. Notably, the presence of PP not only expedited the ignition process but also enhanced the combustion efficiency of the biofuel. In comparison, the co-torrefied hybrid biofuel demonstrated enhanced energy yields, with significant reductions in activation energy, highlighting its potential as an efficient energy source. Torrefaction enriched the biochar structure and led to improved combustion efficiency and a faster burnout rate. Additionally, the torrefaction process also increased biomass calcium content, which resulted in the effective reduction of sulfur dioxide (SO2) emissions. The incorporation of PP also demonstrated superior biomass binding capabilities and amplified pellet quality, when combined with co-torrefaction. Overall, this research underscored the viability of PP as a complementary fuel for FB. When co-torrefied, the resultant hybrid biofuel not only offered enhanced combustion efficiency but also presented an eco-friendly solution, minimizing SO2 emissions and acidic rain potential. This research, therefore, heralded an innovative path towards producing superior quality biomass pellets, minimizing storage and transportation costs, and optimizing energy conversion.